Who Was the First Person Known to Have Discovered Fossils of the Precambrian (Ediacaran) Organism Aspidella terranovica? - Minicucci, Jeffrey (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2017)
This article briefly examines the possible confusion pertaining to the discoveries of Precambrian (Ediacaran) fossils made in the self-governing British colony of Newfoundland in 1868 by the amateur naturalist, the Reverend Moses Harvey, and the subsequent description and naming of the fossil organism Aspidella terranovica in 1872 by Elkanah Billings, the father of Canadian paleontology. Both events could be misinterpreted as one transaction that began with the former event and ended with the latter event. Accounts published by Alexander Murray, the director of the Geological Survey of Newfoundland at the time, arguably may have inadvertently exacerbated the possibility for confusion. The determination of who first discovered fossils of A. terranovica and whose fossil material Billings primarily relied upon when he first described and named the taxon could be placed into doubt as a consequence. Although the confusion does not affect the undisputed priority that Billings holds in having described and named A. terranovica, the opportunity to remedy the confusion serves to benefit the historical record. The incomplete or ambiguous ascertaining and documenting of contextual information whenever an historically significant fossil discovery is made arguably may precipitate subsequent misinterpretations, distortions or omissions in the resulting historical narrative as it develops and becomes entrenched or mythologized in its retelling.